2018
DOI: 10.1186/s13023-018-0790-x
|View full text |Cite
|
Sign up to set email alerts
|

A total pleural covering of absorbable cellulose mesh prevents pneumothorax recurrence in patients with Birt-Hogg-Dubé syndrome

Abstract: BackgroundBirt-Hogg-Dubé syndrome (BHDS) is a recently recognized inherited multiple cystic lung disease causing recurrent pneumothoraces. Similarly to the lesions in patients with lymphangioleiomyomatosis (LAM), the pulmonary cysts are innumerable and widely dispersed and cannot all be removed. We recently described a total pleural covering (TPC) that covers the entire visceral pleura with oxidized regenerated cellulose (ORC) mesh. TPC successfully prevented the recurrence of pneumothorax in LAM patients. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 20 publications
0
8
0
1
Order By: Relevance
“…Pleurodesis appears to reduce the risk of recurrent pneumothorax . We and another Japanese group reported that bioabsorbable pleural coverings successfully protected patients from intractable pneumothoraces . The latter method may enable patients to safely undergo VATS years later if they develop other lung diseases.…”
Section: Lung Manifestation and Therapeutic Approachesmentioning
confidence: 97%
“…Pleurodesis appears to reduce the risk of recurrent pneumothorax . We and another Japanese group reported that bioabsorbable pleural coverings successfully protected patients from intractable pneumothoraces . The latter method may enable patients to safely undergo VATS years later if they develop other lung diseases.…”
Section: Lung Manifestation and Therapeutic Approachesmentioning
confidence: 97%
“…In one retrospective series, the risk of relapse was significantly reduced from >60% with conservative treatment to around 30% after pleurodesis [67]. In another retrospective series reporting the efficacy of surgical pleurodesis with a cellulose mesh covering the visceral pleura, total pleural covering was significantly more effective than lower pleural covering, with 0% versus 42% recurrence rate at 7.5 years [130]. It is important to inform patients about the risk and symptoms of pneumothorax, and to recommend medical assessment in case of new respiratory symptoms such as dyspnoea or chest pain.…”
Section: Management Of Pulmonary Involvementmentioning
confidence: 98%
“…Therefore, we searched and screened 8 articles on the treatment of LAM with thoracoscopic surgery. We meta-analyzed the pneumothorax recurrence rate of LAM in 8 studies [9,[11][12][13][14][15][16] (Table 2).…”
Section: Resultsmentioning
confidence: 99%
“…We conducted a meta-analysis of 8 case reports and experimental studies [9,[11][12][13][14][15][16] showed that VATS treatment of pneumothorax, the recurrence of pneumothorax was reduced compared with conservative treatment (non-surgical treatment control group) [67/174, 95% CI:-0.44[-0.52,-0.36], P<0.00001], statistics also have research meaning. Among them, I 2 >50% (I 2 =81%), we conducted statistical bias analysis.…”
Section: Resultsmentioning
confidence: 99%